Maternal depression and attachment: the evaluation of mother–child interactions during feeding practice - Santona, Alessandra; Tagini, Angela; Sarracino, Diego; De Carli, Pietro; Pace, Cecilia S.; Parolin, Laura; Terrone, Grazia (Frontiers in Psychology, 2015)
Internal working models of attachment (IWM) can moderate the effect of maternal depression on mother-child interactions and child development. Clinical depression pre-dating birthgiving has been found to predict incoherent and less sensitive caregiving. Dysfunctional patterns observed, included interactive modes linked to feeding behaviors which may interfere with hunger-satiation biological rhythms and the establishment of children’s autonomy and individuation. Feeding interactions between depressed mothers and their children seem to be characterized by repetitive interactive failures: children refuse food through oppositional behavior or negativity. The aim of this study was to investigate parenting skills in the context of feeding in mothers with major depression from the point of view of attachment theory. This perspective emphasises parents’ emotion, relational and affective history and personal resources. The sample consisted of 60 mother-child dyads. Mothers were divided into two groups: 30 with Major Depression and 30 without disorders. Children’s age ranged between 12 and 36 months The measures employed were the Adult Attachment Interview and the Scale for the Evaluation of Alimentary Interactions between Mothers and Children. Insecure attachment prevailed in mothers with major depression,, with differences on the Subjective Experience and State of Mind Scales. Groups also differed in maternal sensitivity, degrees of interactive